Evaluation of the Performance of Three Different Methods Used in the Identification of Rigid Body Properties - R.A.B. Almeida; A.P.V. Urgueira; N.M.M. Maia (Shock and Vibration)
The identification of the rigid body properties of a structure is an important matter in various structural dynamic applications, namely in structural modification (coupling/uncoupling), optimization and vibration control. In most situations, the experimental route is the only via to obtain the desired dynamic properties. This goal is achieved by an inverse process which starts from the measurement of Frequency Response Functions (FRFs) and ends on matrices describing the mass distribution of a rigid body.